2019
DOI: 10.1186/s13027-019-0221-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of host immunity with Helicobacter pylori infection in recurrent gastric cancer

Abstract: BackgroundHelicobacter pylori infection is associated with the incidence of gastric cancer. Endoscopic resection has been developed as a proper technique to treat early stage of gastric cancer. However, some patients develop recurrent gastric cancer within 5 years after endoscopic treatment. The aim of the present study is to explore a biomarker for detecting people who has high risk of gastric cancer recurrence.MethodsWe analyzed the Interleukin-10 (IL-10) single nucleotide polymorphism (SNP) and IgG subclass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Helicobacter pylori, which is not only the leading risk factor for gastric cancer but also a high risk of recurrence, colonizes the gastric mucosa and induces persistent chronic gastric inflammation. [21,22] Patients with a genotype of high IgG1 level will have a higher risk of recurrence than patients with other genotypes. Our study demonstrated that SSF3(Helicobacter pylori) is the third leading feature for the recurrence of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori, which is not only the leading risk factor for gastric cancer but also a high risk of recurrence, colonizes the gastric mucosa and induces persistent chronic gastric inflammation. [21,22] Patients with a genotype of high IgG1 level will have a higher risk of recurrence than patients with other genotypes. Our study demonstrated that SSF3(Helicobacter pylori) is the third leading feature for the recurrence of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of gastric cancer is associated with geographical factors, strain diversity, and host immunological responses. The highest incidence of gastric cancer is reported in East Asian countries [16]. In 2017, there were 1.22 million new cases of gastric cancer with 865.000 deaths and 19.1 million disability-adjusted life-years.…”
Section: Epidemiology and Burden Of H Pylori Infectionmentioning
confidence: 99%
“…Defects in gene coding IL-1 and TNF are associated with decreased cytokines production and Immunology of Helicobacter pylori Infection DOI: http://dx.doi.org/10.5772/intechopen.104592 increased risk for gastric cancer [7]. Single nucleotide polymorphism in gene coding IL-10 which resulted in increased IL-10 will promote Th2 activity and resulted in prolonged H. pylori infection and an elevated risk for recurrent gastric cancer [16]. The presence of H. pylori in the macrophages alters the expression of miRNA.…”
Section: Mechanism Of Immune Evasion Of H Pylorimentioning
confidence: 99%
“…Genetic constituents also assumed as a significant cause in gastric carcinogenesis; might be due to alteration in the expression of normal genes, resulted in phenotypic malignancy [17,18]. Hence, the time to time studies on H. pylori in relation to genetic and environmental risk factors are required to uncoil the complexity of this disease.…”
Section: Pathogenesis Of Gastric Cancermentioning
confidence: 99%